Analisis Hukum Dampak Pelaku Usaha Grosir Terhadap Penjualan Produk yang Terafiliasi dengan Israel Perspektif KHES: Studi Kasus Kota Tanjungbalai - M. Rahul Fauzan Saragih; Annisa Sativa (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
With the publication of MUI Fatwa Number 83 of 2023 concerning the Law on Support for the Palestinian People, there have also been many calls to join in boycotting products affiliated with Israel. This causes quite serious problems for wholesale business actors who sell products that people need in their daily lives. This research aims to explain legal protection for business actors who experience losses due to the issuance of MUI Fatwa No. 83 of 2023 and how KHES regulates the protection itself. This research method was carried out using an empirical juridical method, so the method used was a field method, namely research carried out in the field which aims to obtain information and describe events, incidents with facts found in the field. Data analysis was carried out qualitatively, involving observation and in-depth study of the data obtained. The primary data used comes from the field, in this case there are interviews from wholesale business actors. Meanwhile, secondary data is data obtained from the literature. Research shows that many wholesale businesses suffer losses due to the boycott of products affiliated with Israel. From the perspective of the Compilation of Sharia Economic Law, wholesale business actors who experience losses are the risks they bear, the government should pay more attention to the impact on wholesale business actors who experience losses so that products affiliated with Israel are replaced with other brands.